2008
DOI: 10.1088/0022-3727/41/19/194010
|View full text |Cite
|
Sign up to set email alerts
|

Local deposition of SiOxplasma polymer films by a miniaturized atmospheric pressure plasma jet (APPJ)

Abstract: An atmospheric plasma jet (APPJ, 27.17 MHz, Ar with 1% HMDSO) has been studied for the deposition of thin silicon-organic films. Jet geometries are attractive for local surface treatment or for conformal covering of 3D forms, e.g. inner walls of wells, trenches or cavities, because they are not confined by electrodes and their dimensions can be varied from several centimetres down to the sub-millimetre region. Deposition experiments have been performed on flat polymer and glass samples with a deposition rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
111
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 16 publications
8
111
0
Order By: Relevance
“…The jet has to be driven with higher working gas flows compared to the former work [7] , and moderate to high powers to achieve these operational conditions. The discharge then develops three spatially relatively immobile filaments, which are in contact with the substrate and give the impression of constricted, high current 'hot' filaments with a high plasma density.…”
Section: Resultsmentioning
confidence: 99%
“…The jet has to be driven with higher working gas flows compared to the former work [7] , and moderate to high powers to achieve these operational conditions. The discharge then develops three spatially relatively immobile filaments, which are in contact with the substrate and give the impression of constricted, high current 'hot' filaments with a high plasma density.…”
Section: Resultsmentioning
confidence: 99%
“…), plasma enhanced chemical vapour deposition (PECVD) of thin films, plasma decontamination of toxic compounds, and recently in biomedical application and plasma medicine [1][2][3][4][5][6]. The dielectric barrier discharges (DBD) [1,2] and atmospheric pressure plasma jets (APPJ) [7] belong to the most successful designs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the flow regime of plasma jet can enhance the delivery of active species from the active plasma zone to the treated sample. In comparison to the other atmospheric pressure plasma sources the treated surface could be then placed farther [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The films are deposited using the recently observed homogenized plasma mode (locked mode) which is characterized by regularly ordered and moving discharge filaments. [6] It could be shown that this discharge mode in conjunction with a symmetric mixing of the vaporized precursor with the surrounding cylindrically rotating plasma at the outlet of the capillary leads to a significantly enhanced homogeneity of the profile and chemical composition of the deposited films as compared to a plasma jet with irregular discharge filaments. [6] SiO x films with exceptionally low carbon content and a high degree of cross-linkage could be deposited using OMCTS [octamethylcyclotetrasiloxane, Si 4 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[6] It could be shown that this discharge mode in conjunction with a symmetric mixing of the vaporized precursor with the surrounding cylindrically rotating plasma at the outlet of the capillary leads to a significantly enhanced homogeneity of the profile and chemical composition of the deposited films as compared to a plasma jet with irregular discharge filaments. [6] SiO x films with exceptionally low carbon content and a high degree of cross-linkage could be deposited using OMCTS [octamethylcyclotetrasiloxane, Si 4 8 ]. An experimental study on the influence of the O 2 versus OMCTS concentration on the chemical composition of the films and their radial gradients over the static deposition profile is carried out by means of XPS and ATR-FTIR.…”
Section: Introductionmentioning
confidence: 99%